2009
DOI: 10.1007/s11746-009-1479-z
|View full text |Cite
|
Sign up to set email alerts
|

Human Milk Fat Substitute from Butterfat: Production by Enzymatic Interesterification and Evaluation of Oxidative Stability

Abstract: Recent data have suggested that the fatty acid composition and molecular structure of fats in infant formulas should be as similar to human milk fat as possible to obtain optimal fat and calcium absorption from the infant formula. This work investigated the possibilities of using enzyme technology and butterfat as a material to produce a fat similar to human milk fat with respect to the above parameters. Moreover, the oxidative stability of the enzyme modified human milk fat substitute (HMFS) was compared to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 15 publications
1
28
0
Order By: Relevance
“…Milk fat is a natural product from the dairy industry. Even though its composition and structure are significantly different from HMF, milk fat has a lot in common with mother's milk fat in terms of content of MUFA and minor fatty acids such as conjugate linoleic acid [2,32]. In order to enrich TAG derived from MF or L in PUFA, the enzymatic interesterification was used.…”
Section: Fatty Acids Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…Milk fat is a natural product from the dairy industry. Even though its composition and structure are significantly different from HMF, milk fat has a lot in common with mother's milk fat in terms of content of MUFA and minor fatty acids such as conjugate linoleic acid [2,32]. In order to enrich TAG derived from MF or L in PUFA, the enzymatic interesterification was used.…”
Section: Fatty Acids Compositionmentioning
confidence: 99%
“…In general, most studies have reported a decrease in oxidative stability of SL like HMFS compared to the initial fats [6,40]. Sørensen et al [32] have reported that the oxidative stability of the HMFS obtained from interesterified mixture of milk fat, rapeseed oil, and soybean oil was lower than that of the reference oil with the same fatty acid composition. Therefore, the unsaturated fatty acids in HMFS can be oxidized into hydroperoxides (primary oxidation products), which can then be rapidly decomposed to secondary oxidation products such as alkanes, alkenes, aldehydes, and ketones.…”
Section: Oxidative Stabilitymentioning
confidence: 99%
“…Human milk fat provides a major source of energy as well as the required nutrients (Yang, Xu, He, & Li, 2003). The studies conducting fatty acid composition and distribution in triacylglycerols (TAGs) in infant formulas resulted in the development of human milk fat substitutes to mimic milk fat composition (Sahin, Akoh, & Karaali, 2005;Sørensen, Xu, Zhang, Kristensen, & Jacobsen, 2009;Yang et al, 2003). Human milk fat substitutes have been developed by producing structured lipids defined as modified TAGs.…”
Section: Introductionmentioning
confidence: 99%
“…Structured lipids contain mixture of fatty acids (short, medium and long fatty acids) located in same glycerol backbone. Enzymatic or chemical interesterifications are utilized to produce structured lipids (Sørensen et al, 2009). Vegetable oils (palm, soybean, hazelnut and amaranth oil), lard, butter and tripalmitin have been used as substrate to produce human milk fat substitutes.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, for example, Yang et al [23] obtained TAGs with 71% PA at sn-2 position and 44% oleic acid at sn-1,3 positions, by acidolysis of lard and free fatty acids from soybean oil; this reaction was carried out at 61 ºC and using Lipozyme RM IM as 1,3 specific lipase. Sorensen et al [24] also produced TAGs with a molecular structure and fatty acid composition very similar to that of human milk fat, by acidolysis of butterfat and a mixture of rapeseed and soybean oil fatty acids, catalyzed by Lipozyme RM IM, at 65·ºC; these TAGs contained 46-56% PA at sn-2 position and 31-35% oleic acid of total fatty acids. After the acidolysis reaction these TAGs were purified by short path distillation and, therefore, also in absence of solvent.…”
Section: Introductionmentioning
confidence: 99%